Portrayal of Muslim and Western Women In Hollywood Movies - Dr. Abida Noureen; Jabeen, Dr. Shehla; Fareed, Fazal (Journal of Peace, Development and Communication, 2021)
Hollywood is the largest and oldest media industry in the World. This study points out the role and depiction of Muslim as well Western women in the same movies. A qualitative textual analysis of movies examined specific characteristics themes and scenes which were being displayed by Muslim/Western Women characters under the theory of Orientalism These characteristics included, traditional/native attire, acts of hostility and aggression, affiliation with terrorism, depicted as victimizers or victims.